APPLICATIONS IN NUTRITION SERVICES POLY RS. PELNI "PETAMBURAN" USING VISUAL BASIC 6.0 - Dodi Rahman; Rahayu Noveandini, Skom, MMSI Rahayu Noveandini, Skom, MMSI (Jurnal Sistem Informasi, 2005)
Scientific writing is about how to make the application of poly nutrition services byusing Visual Basic 6.0.In scientific writing database is also used by Visual Data Manager (VisData) that hasbeen integrated in Visual Basic 6.0 program itself and the use of Crystal Reports 8.5to display the report be printed.Scientific writing is also equipped with a hierarchical view of the program andflowchart of the application. This application displays the main menu which providesthe names of diseases diet, display the distribution of food a day, food that should beon abstinence and sample daily menus. This application was made aiming to help aconsulting nutritionist in the service to patients quickly and accurately. With thisprogram the service to patients can be improved.